PREFACE. - Papi, Marcella Bertuccelli; de Mendoza Ibáñez, Francisco José Ruiz (Textus, 2010)
An introduction to topics discussed within the issue is presented, giving particular focus on different aspects of language representation and language that are compatible with a neuro-cognitive perspective, including an article on the notion of illocutionary construction, another on the conceptual representations or images of words in trilingualism, and an article on grammatical alternation.